Pemanfaatan Energi Matahari pada Solar Panel untuk Penerangan Jalan dan Jalur Hijau Di RW 12 Desa Landungsari - Irwan Heryanto/Eryk; Mohammad Noor Hidayat; Sigit Setya Wiwaha; Ika Noer Syamsiana (Elposys: Jurnal Sistem Kelistrikan, 2020)
To assist residents of RW 12 Desa Landungsari in supporting village facilities and infrastructure, especially the problem of street lighting. Where to apply to the related agency is not possible because it is only a rural area, so it is necessary to have the self-help of the residents in lighting up their area at night. This lighting will use solar cells as an energy source with a capacity of 50 Wp Off Grid system with a load of 12 Volt DC LED lights. This is because solar energy is a large enough energy available and is environmentally friendly.This research activity also includes community education on the importance of using solar energy as a source of electrical energy. Based on field testing, the average solar panel output voltage is 17 volts, the maximum charging current is 2.6 A and a load power of 30 watts consists of several LED lights.